2007
DOI: 10.1080/00288230709510283
|View full text |Cite
|
Sign up to set email alerts
|

Developing variable rate application technology: Economic impact for farm owners and topdressing operators

Abstract: The use of variable rate application technology on topdressing aircraft is now technically possible. Its uptake will be determined by the economic benefit to the farmers and pricing structure for aerial operators. The economic impact of six fertiliser spreading scenarios were examined at a case study farm. Farm operating costs were considered under each of the scenarios and the economic consequences calculated. Variable rate application was found to be financially viable, both in terms of maximising return per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…They reported that the annual pasture production could be increased between 6.5-24.4% by VRF. They also conducted an economic analysis on implementing VRF over the blanket application where they found that this technique could increase 26% annual cash returns per hectare [45]. These findings clearly indicate the potential to improve fertilizer use efficiency and the economic benefits, as well as to reduce the risk of fertilizer wastage contaminating the environment from VRF [38].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the annual pasture production could be increased between 6.5-24.4% by VRF. They also conducted an economic analysis on implementing VRF over the blanket application where they found that this technique could increase 26% annual cash returns per hectare [45]. These findings clearly indicate the potential to improve fertilizer use efficiency and the economic benefits, as well as to reduce the risk of fertilizer wastage contaminating the environment from VRF [38].…”
Section: Discussionmentioning
confidence: 99%
“…GPS mapping and guidance ‘Autosteer’, yield mapping, robotic milking, RFID tagging, electromagnetic sensor mapping). The findings of this review led to further PA research in variable rate fertiliser application to hill country by top‐dressing and to flat land by ground spreading…”
Section: Early Studies Scoping the Potential Application Of Precisionmentioning
confidence: 92%
“…A study was conducted to investigate the potential use of precision technologies by hill country farming communities . It assessed the potential benefits from automating fertiliser flow control from top‐dressing planes to vary application rates based on the potential outputs of the farmland.…”
Section: Precision Agriculture At the Landscape Scale: Assessing Vratmentioning
confidence: 99%
See 1 more Smart Citation
“…with high slope). Such considerations would be of value in implementing the variable fertiliser rate approach advocated by Murray & Yule (2007). Additional factors to be considered in such exercises include the ease of management of land management units as influenced by topography and spatial location; the versatility of the soils; and the nature of the livestock enterprises that can be run on the units.…”
Section: Fertiliser Treatments and Pasture Productionmentioning
confidence: 98%